Aspergillus fumigatus mitogen-activated protein kinase MpkA is involved in gliotoxin production and self-protection - Fleming, Alastair (My University, 2024)
Aspergillus fumigatus is a saprophytic fungus that can cause a variety of human diseases known as aspergillosis. Mycotoxin gliotoxin (GT) production is important for its virulence and must be tightly regulated to avoid excess production and toxicity to the fungus. GT self-protection by GliT oxidoreductase and GtmA methyltransferase activities is related to the subcellular localization of these enzymes and how GT can be sequestered from the cytoplasm to avoid increased cell damage. Here, we show that GliT:GFP and GtmA:GFP are localized in the cytoplasm and in vacuoles during GT production. The Mitogen-Activated Protein kinase MpkA is essential for GT production and self-protection, interacts physically with GliT and GtmA and it is necessary for their regulation and subsequent presence in the vacuoles. The sensor histidine kinase SlnASln1 is important for modulation of MpkA phosphorylation. Our work emphasizes the importance of MpkA and compartmentalization of cellular events for GT production and self-defense.
PUBLISHED
Keywords: Aspergillus fumigatus; saprophytic fungus; aspergillosis; Aspergillus fumigatus; saprophytic fungus; aspergillosis